Borderline lepromatous leprosy mimicking lupus vasculitis: a rare case report from the Brazilian Amazon - Carolina Souza-de Oliveira; Isabella C. Mendes-Alexandre; Laísa Ezaguy-de Hollanda; Rebeca Martins; Vanessa Ribeiro-Ferreira; João V. Chagas-Rossin; Hitesh Babani; Luciana Mendes-dos Santos (Revista da Sociedade Portuguesa de Dermatologia e Venereologia)
Leprosy is a neglected chronic infectious disease that is endemic in Brazil. It has a heterogeneous clinical presentation and often mimics other diseases, such as collagenosis, leading to underdiagnosis, incorrect treatment, and high morbidity. This report presents the case of a 40-year-old patient with erythematous-violaceous patches and papules on the lower limbs, simulating lupus vasculitis, associated with criteria for systemic lupus erythematosus, with no clinical improvement despite treatment. High suspicion and knowledge of the disease are necessary for early diagnosis, leprosy screening, and prevention of sequelae.